METODE PEMBELAJARAN DALAM MODEL PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR & MADRASAH IBTIDAIYAH - Hana fauziah; Nurul Hasanah; Nurfitria; Satria Galuh Permana; Muzaqi M. Roudhotul Ridwan (Bajang Institute, 2024)
Learning is an activity that involves students and teachers to achieve learning goals, so it is necessary to choose the right learning method or model because learning methods function as a tool or way to achieve learning goals. In this regard, learning objectives should have been developed based on three domains, namely cognitive, affective these learning methods and learning models are for learning indonesian in MI/SD. Therefore, the author tries to dig up information about learning methods and learning models through various e-book and journal media using the literature study method. The aim is for educators to know and understand the various learning models that can be carried out or used for learning indonesian in MI/SD. And from the results of this literature study, it was found that various learning methods and learning models can be applied to indonesian language learning. In the past, it was also discovered which was part of the mention of learning approaches or models and learning methods.